The answer is .52
glad 2 help
Answer:
Given expression:
![\dfrac{14a^4b^6c^{-10}}{8a^{-2}b^3c^{-5}}](https://tex.z-dn.net/?f=%5Cdfrac%7B14a%5E4b%5E6c%5E%7B-10%7D%7D%7B8a%5E%7B-2%7Db%5E3c%5E%7B-5%7D%7D)
Separate the variables:
![\implies \dfrac{14}{8} \cdot \dfrac{a^4}{a^{-2}} \cdot \dfrac{b^6}{b^3} \cdot \dfrac{c^{-10}}{c^{-5}}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B14%7D%7B8%7D%20%5Ccdot%20%5Cdfrac%7Ba%5E4%7D%7Ba%5E%7B-2%7D%7D%20%5Ccdot%20%5Cdfrac%7Bb%5E6%7D%7Bb%5E3%7D%20%5Ccdot%20%5Cdfrac%7Bc%5E%7B-10%7D%7D%7Bc%5E%7B-5%7D%7D)
Reduce the first fraction:
![\implies \dfrac{7}{4} \cdot \dfrac{a^4}{a^{-2}} \cdot \dfrac{b^6}{b^3} \cdot \dfrac{c^{-10}}{c^{-5}}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B7%7D%7B4%7D%20%5Ccdot%20%5Cdfrac%7Ba%5E4%7D%7Ba%5E%7B-2%7D%7D%20%5Ccdot%20%5Cdfrac%7Bb%5E6%7D%7Bb%5E3%7D%20%5Ccdot%20%5Cdfrac%7Bc%5E%7B-10%7D%7D%7Bc%5E%7B-5%7D%7D)
![\textsf{Apply Division Property of Exponents rule} \quad \dfrac{a^b}{a^c}=a^{b-c}:](https://tex.z-dn.net/?f=%5Ctextsf%7BApply%20Division%20Property%20of%20Exponents%20rule%7D%20%5Cquad%20%5Cdfrac%7Ba%5Eb%7D%7Ba%5Ec%7D%3Da%5E%7Bb-c%7D%3A)
![\implies \dfrac{7}{4} \cdot a^{4-(-2)} \cdot b^{6-3} \cdot c^{-10-(-5)}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B7%7D%7B4%7D%20%5Ccdot%20a%5E%7B4-%28-2%29%7D%20%5Ccdot%20b%5E%7B6-3%7D%20%5Ccdot%20c%5E%7B-10-%28-5%29%7D)
![\implies \dfrac{7}{4} \cdot a^{6} \cdot b^{3} \cdot c^{-5}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B7%7D%7B4%7D%20%5Ccdot%20a%5E%7B6%7D%20%5Ccdot%20b%5E%7B3%7D%20%5Ccdot%20c%5E%7B-5%7D)
![\textsf{Apply Negative Property of Exponents rule} \quad a^{-n}=\dfrac{1}{a^n}](https://tex.z-dn.net/?f=%5Ctextsf%7BApply%20Negative%20Property%20of%20Exponents%20rule%7D%20%5Cquad%20a%5E%7B-n%7D%3D%5Cdfrac%7B1%7D%7Ba%5En%7D)
![\implies \dfrac{7}{4} \cdot a^{6} \cdot b^{3} \cdot \dfrac{1}{c^5}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B7%7D%7B4%7D%20%5Ccdot%20a%5E%7B6%7D%20%5Ccdot%20b%5E%7B3%7D%20%5Ccdot%20%5Cdfrac%7B1%7D%7Bc%5E5%7D)
Therefore:
![\implies \dfrac{7a^6b^3}{4c^5}](https://tex.z-dn.net/?f=%5Cimplies%20%5Cdfrac%7B7a%5E6b%5E3%7D%7B4c%5E5%7D)
Alright, we can turn the word problem at the beginning into an equation.
Let's represent oregano with "o" and peppercorns as "p".
o=p+17
Also, we know that the two added together are 253 pounds.
o+p=253
Since we know that o=p+17, let's substitute it into the second equation.
(p+17)+p=253
2p+17=253
-17 -17
2p=236
p=118
So, we have 118 pounds of peppercorns. (Although it's irrelevant to the second half of the equation, we also know we have 135 pounds of oregano)
Now, let's convert pounds to ounces.
1 pound = 16 ounces.
So, multiply 118 by 16....
118*16=1888
So, you can make 1888 one-ounce bags of peppercorns.
2a
tan37=r/8
r=8tan37
r≈6 in rise per step (to nearest whole inch)
2b
11*12/6=22 steps needed to climb the 11 ft to the entrance
...
3a
tanα=14/20
α=arctan(7/10)
α≈35° (to nearest whole degree)
..
3b
tanα=21/17
α=arctan(21/17)
α≈51° (to nearest degree)
Answer:
easy it is 100 trust me
Step-by-step explanation: